NEGARA HUKUM, PROGRAM LEGISLASI NASIONAL DAN KEBUTUHAN DESAIN BESAR BAGI PERENCANAANNYA - Bambang Kesowo (Arena Hukum, 2012)
AbstractThe question of whether the State of Indonesia is a State law have to answered by using indicators ofjustice for everyone without any discrimination, rule of law through the establishment of laws, alsorespect and protection of human rights. Indonesian Constitution of 1945 in Article 1 paragraph (3)states that